Analyst’s Perception on the Use of AI-based Tools in the Software Development Life Cycle - Rafi Giffari; M. Mushlih Ridho; Dana Indra Sensuse; Deden Sumirat Hidayat; Erisva Hakiki Purwaningsih (Faculty of Computer Science Universitas Indonesia, 2024)
Artificial Intelligence (AI) integration has been the goal in many industries, including in the software development industry. One example of this integration comes in the form of integrating AI in the Software Development Lifecycle (SDLC). To date, the difficulties of incorporating AI-based tools into particular phases of SDLC have not received much attention in research. Using qualitative approach, this study aims to discover the perception on the use of AI-based tools and challenges in integrating them in the analysis phase of SDLC. The study finds out that analyst have positive perception about integrating this technology in their field of work but there are some challenges while integrating this technology such as data security and reliability concern, dependency, and adapting to this technology. This study also discovers some key factors of why some analysts adopt or refuse this technology namely time, urgency, budget, and insecurities of the users.